Perencanaan Produksi Agregat Dengan Metode Goal Programing - Mastiadi Tamjidillah (INFO-TEKNIK, 2003)
A Production planning is very important to all activities in manufacturing company. For a company producing a variety of product the production planning will be complicated. In this case it’s necessary to make an aggregate production planning. A Company has goals to achieve the products, althought there differenciate between each other. Other wise, if needs to make a production planning that accommodate such goals.Goal programming model  can be used for aggregate production planning. This multi objective model can accommodate more than one goal which will be achieved by the company. Product demand forecasting is input for aggregate production planning. From this aggregate production planning, futhermore, disaggregation must be conducted, then it will be continued by raw material planning. The raw material planning is made by lot size each order economically.   The aim of goal programming model is to maximize profits, to minimize subcontract products amount, to minimize overtime labours cost and to minimize inventory amount. The results show that the goal programming model could accommodate three goals that will be achieved by the company, except that goal to maximize profit high goal is to minimize inventory amount. The comparison between planning and realitation show that the goal programming model could reduce the minimize overtime labours cost.